Laparoscopic Bullet Removal in a Penetrating Abdominal Gunshot - Stefanou, Christos (Case Rep Surg, 2016)
Penetrating abdominal trauma has been traditionally treated by exploratory laparotomy. Nowadays laparoscopy has become an accepted practice in hemodynamically stable patient without signs of peritonitis. We report a case of a lower anterior abdominal gunshot patient treated laparoscopically. A 32-year-old male presented to the Emergency Department with complaint of gunshot penetrating injury at left lower anterior abdominal wall. The patient had no symptoms or obvious bleeding and was vitally stable. On examination we identified 1 cm diameter entry wound at the left lower abdominal wall. The imaging studies showed the bullet in the peritoneal cavity but no injured intraperitoneal and retroperitoneal viscera. We decided to remove the bullet laparoscopically. Twenty-four hours after the intervention the patient was discharged. The decision for managing gunshot patients should be based on clinical and diagnostic findings. Anterior abdominal injuries in a stable patient without other health problems can be managed laparoscopically.